2017
DOI: 10.1098/rsos.170331
|View full text |Cite
|
Sign up to set email alerts
|

Humans permanently occupied the Andean highlands by at least 7 ka

Abstract: High-elevation environments above 2500 metres above sea level (m.a.s.l.) were among the planet's last frontiers of human colonization. Research on the speed and tempo of this colonization process is active and holds implications for understanding rates of genetic, physiological and cultural adaptation in our species. Permanent occupation of high-elevation environments in the Andes Mountains of South America tentatively began with hunter–gatherers around 9 ka according to current archaeological estimates, thoug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 40 publications
3
24
0
1
Order By: Relevance
“…Historical records indicate that the Oromo tribe of Ethiopia has only been settled in the highlands for ß500 years (Hassen, 1990;Lewis, 1966); however, the Amhara tribe has been living at altitude for potentially up to 70,000 years based on archaeological evidence (Aldenderfer, 2003;Pleurdeau, 2005;Aldenderfer, 2006;Simonson, 2015;Ossendorf, 2019). Humans are thought to have occupied the Tibetan plateau for ß30,000-40,000 years (Zhang et al 2018), and eventually crossed a land bridge that once connected present day Russia and Alaska, which facilitated North and South American settlement and eventual migration to the Andes ß7000-10,000 years ago (Aldenderfer, 2008;Haas et al 2017). technique has yet to be completed at high altitude likely due to its invasive nature and need for adequate highly trained medical support. The study by Berger and colleagues (2005) found that endothelium-dependent vasodilatation in response to intra-arterial (brachial) infusion of acetylcholine was impaired in high altitude pulmonary oedema-susceptible patients (exaggerated hypoxic pulmonary vasoconstriction), but preserved in control participants following 4 h of 12% O 2 (ß4500 m equivalent; Berger et al 2005).…”
Section: Figure 1 Timeline Summary Of the Proposed Ethiopian Tibetamentioning
confidence: 99%
See 2 more Smart Citations
“…Historical records indicate that the Oromo tribe of Ethiopia has only been settled in the highlands for ß500 years (Hassen, 1990;Lewis, 1966); however, the Amhara tribe has been living at altitude for potentially up to 70,000 years based on archaeological evidence (Aldenderfer, 2003;Pleurdeau, 2005;Aldenderfer, 2006;Simonson, 2015;Ossendorf, 2019). Humans are thought to have occupied the Tibetan plateau for ß30,000-40,000 years (Zhang et al 2018), and eventually crossed a land bridge that once connected present day Russia and Alaska, which facilitated North and South American settlement and eventual migration to the Andes ß7000-10,000 years ago (Aldenderfer, 2008;Haas et al 2017). technique has yet to be completed at high altitude likely due to its invasive nature and need for adequate highly trained medical support. The study by Berger and colleagues (2005) found that endothelium-dependent vasodilatation in response to intra-arterial (brachial) infusion of acetylcholine was impaired in high altitude pulmonary oedema-susceptible patients (exaggerated hypoxic pulmonary vasoconstriction), but preserved in control participants following 4 h of 12% O 2 (ß4500 m equivalent; Berger et al 2005).…”
Section: Figure 1 Timeline Summary Of the Proposed Ethiopian Tibetamentioning
confidence: 99%
“…Andean highlanders with and without chronic mountain sickness. There is good evidence that the Andean plateau has been populated for at least 7000 years (Aldenderfer, 2008;Haas et al 2017). The Quechua and Aymara populations of this region present with what can be considered an exaggerated form of typical lowlander high altitude adaptation with increased [Hb] levels and haematocrit, together increasing the oxygen content in arterial blood, so that it actually exceeds that of lowlanders at sea level (Beall, 2007).…”
Section: Impact Of Hypoxia On Endothelial Function In Highlandersmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, tropical Andean highlands have a long history of human occupation and habitat transformation. Here, early settlements of hunters-gatherers date to as far back as 11 000 years BP (van der Hammen and Urrego 1978, Rademaker et al 2014Rademaker et al , 2016, or even earlier (Jolie et al 2011), and became permanent after 9000 years BP (Haas et al 2017), when environmental conditions favored the development of agriculture (Pearsall 2008). In fact, our study area encompasses one of the centers of origin of cultivated plants (Vavilov et al 1992, Spooner et al 2005, Pearsall 2008, Hardigan et al 2017) and animal domestication (Stahl 2003, Yacobaccio andVilá 2016).…”
Section: Study Areamentioning
confidence: 95%
“…Here, early settlements of hunters-gatherers date to as far back as 11 000 years BP (van der Hammen and Urrego 1978, Rademaker et al 2014Rademaker et al , 2016, or even earlier (Jolie et al 2011), and became permanent after 9000 years BP (Haas et al 2017), when environmental conditions favored the development of agriculture (Pearsall 2008). Here, early settlements of hunters-gatherers date to as far back as 11 000 years BP (van der Hammen and Urrego 1978, Rademaker et al 2014Rademaker et al , 2016, or even earlier (Jolie et al 2011), and became permanent after 9000 years BP (Haas et al 2017), when environmental conditions favored the development of agriculture (Pearsall 2008).…”
Section: Study Areamentioning
confidence: 99%